Nanoscale redistribution of alloying elements in high-burnup AXIOM-2 (X2®) and their effects on in-reactor corrosion. (September 2021) - Yu, Zefeng; Bachhav, Mukesh; Teng, Fei; He, Lingfeng; Couet, Adrien
Graphical abstract: Highlights: Native Nb-rich precipitates and IIPs exist in both the oxide and metal of high-burnup X2®. Fe-rich transition cracks and Fe-rich oxide grain boundaries were observed. The Nb concentration in the metal solid solution at 4 cycles has been reduced to about 0.15 at.%. Nb content in the oxide may be rejected back into the metal matrix. Abstract: A comprehensive characterization study was carried out on 1 and 4 cycles X2®, aiming to reveal effect of irradiation-induced alloying element redistribution on the in-reactor corrosion kinetics. Using a combination of (scanning) transmission electron microscopy ((S)/TEM) and atom probe tomography (APT), the results strongly evidenced the existence of Nb-rich native precipitates and irradiation-induced platelets (IIPs)/nanoclusters in both metal and oxide. In addition, the suboxide may reject Nb content back into the metal matrix to achieve a thermodynamic equilibrium state. On the other hand, Fe-rich transition cracks were observed for the first time, along with Fe-rich oxide grain boundaries.